2008
DOI: 10.1364/oe.16.013391
|View full text |Cite
|
Sign up to set email alerts
|

Quantum efficiency enhancement in film by making nanoparticles of polyfluorene

Abstract: Abstract:We report on conjugated polymer nanoparticles of polyfluorene that were formed to exhibit higher fluorescence quantum efficiency in film (68%) and reduce undesired emission peak wavelength shifts in film (by 20 nm), compared to the solid-state polymer thin film made directly out of the same polymer solution without forming nanoparticles. Using the facile reprecipitation method, solutions of poly[9,9-dihexyl-9H-fluorene] in THF were added at different volume ratios to obtain different size distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Collapse of polymer chains into nanoscale spherical particles results in red-shifted emission spectra by over 10 to 41 nm depending on the particle size and type of polymer being folded, as we described recently [22]. Figure 3 shows the changes in peak position of PF and MEH-PPV from their solution to nanoparticle dispersion states.…”
Section: Investigation Of Photophysical Properties Of Nanoparticlesmentioning
confidence: 52%
See 2 more Smart Citations
“…Collapse of polymer chains into nanoscale spherical particles results in red-shifted emission spectra by over 10 to 41 nm depending on the particle size and type of polymer being folded, as we described recently [22]. Figure 3 shows the changes in peak position of PF and MEH-PPV from their solution to nanoparticle dispersion states.…”
Section: Investigation Of Photophysical Properties Of Nanoparticlesmentioning
confidence: 52%
“…For sample a as the PF layer is thicker we observe an emission at 425 nm, which shows that PF did not form separate NPs emitting normally at 429 nm. PF in sample b on the other hand emits at 419 nm, which shows really how thin the PF layer on the inner MEH-PPV domain is, so that its emission characteristics have almost not changed in comparison to the PF solution [22]. A second evidence for the verification of the resulting structure is also the slightly blue-shifting MEH-PPV emission at PLE of PF, which shows that PF and MEH-PPV domains are in very close proximity.…”
Section: Systems 3 Andmentioning
confidence: 84%
See 1 more Smart Citation
“…Near-infrared fluorescent particles are useful to circumvent interference from autofluorescence in biological tissues. Demir and co-workers [222] have carried out comparison studies and found that the quantum efficiency of small NPs (up to 30 nm in diameter, high fluorescence quantum efficiency of Φ PL = 68%) of PF-01a significantly surpass the efficiency observed for solid-state thin films without forming nanoparticles (Φ PL = 23%). Emission intensity obviously depends on the film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…6−12 One of the most attractive features of CPNs is the convenient tunability and control of their properties through the choice and functionalization of the polymer and the surface modification of nanoparticles. Furthermore, CPNs exhibit low toxicity, 13 and their mechanical stability can be enhanced through cross-linking.14 Their optical properties arise from the controlled conformational changes of the polymer and their aggregation form rather than the quantum confinement effects, in contrast with inorganic nanoparticles, for example, colloidal semiconductor quantum dots (QDs).13 As a result of these attractive properties, CPNs find use as alternative color convertors, or molecular beacons, in various biotechnology 1,3,4 and optoelectronic applications. 6,9,10,13,14 The emission of color convertors, including CPNs, can be enhanced via the Forster-type nonradiative energy transfer (NRET) (also dubbed as Forster resonance energy transfer, FRET), which basically relies on the exciton−exciton interactions between the donor and acceptor emitters.…”
mentioning
confidence: 99%